Ultrasensitive heterogeneous bioaffinity assays by eliminating nonspecific binding of upconverting nanoparticles - Kuusinen, Saara (fi=Turun yliopisto|en=University of Turku|, 2025)
Bioaffinity assays are commonly used for specific detection of biomarkers in biological samples. Reducing the lowest detectable concentration, i.e. the analytical sensitivity of such assays, is beneficial for several reasons: it allows for earlier diagnostics of various diseases, enables introduction of new biomarkers and decreases the sample volume required for the analysis. Upconverting nanoparticles (UCNPs) have attracted wide interest as labels in sensitive bioaffinity assays due to their unique optical properties that enable the detection of trace amounts of UCNPs with relatively simple instrumentation. However, the background signal originating from the nonspecific binding of UCNP conjugates has hindered reaching ultrasensitivity that is required for detecting extremely low-abundance biomarkers. The aim of this research was to improve the analytical sensitivity that can be achieved by upconversion-based bioaffinity assays, particularly by reducing the nonspecific binding of UCNP conjugates. The study included both, immunoassays and oligonucleotide hybridization assays. The plasma matrix related nonspecific binding of UCNP conjugates in immunoassays was studied by isolating the fractions of human plasma associated with elevated nonspecific binding and identifying the contents of the fractions by mass spectrometry. In hybridization assays, the probe hybridization stability with a short target sequence was enhanced by exploiting base stacking interactions using hairpin-structured DNA probes. Additionally, a novel hybridization complex transfer technique was developed to eliminate the nonspecific binding of UCNP conjugates on the detection surface. A major part of plasma-related nonspecific binding in immunoassays was associated with complement component C1q. The background signal was strongly reduced by increasing the salt concentration in the assay buffer or by adding heparin as a polyanionic blocker. In hybridization assays, the hairpin-structured probes improved the analytical sensitivity by a factor of 18 compared to the corresponding linear probes. Moreover, the complex transfer procedure eliminated the backgroud signal from the nonspecifically bound UCNP conjugates, making the detection instrument the main sensitivity-limiting factor. The hybridization assays reached femto-attomolar detection limits for DNA analogue of miR-20a, making them promising tools for micro-RNA based diagnostics.

Ultraherkkiä heterogeenisiä bioaffiniteettimäärityksiä käänteisviritteisten nanopartikkelien epäspesifisen sitoutumisen poistolla Bioaffiniteettimäärityksiä käytetään yleisesti biomerkkiaineiden spesifiseen havaitsemiseen biologisista näytteistä. Matalimman määrityksillä mitattavissa olevan pitoisuuden eli analyyttisen herkkyyden alentaminen on hyödyllistä monesta syystä: se mahdollistaa sairauksien diagnosoinnin varhaisemmassa vaiheessa, uusien biomerkkiaineiden käyttöönoton ja pienempien näytetilavuuksien käytön. Käänteis-viritteiset nanopartikkelit (engl. upconverting nanoparticles, UCNP) ovat herättäneet kiinnostusta tällaisten määritysten leimoina, koska niiden optiset ominaisuudet mahdollistavat äärimmäisen alhaisten leimamäärien havaitsemisen verrattain yksinkertaisella laitteistolla. UCNP:iden epäspesifisestä sitoutumisesta johtuva taustasignaali on kuitenkin estänyt ultraherkkien määritysten kehittämisen. Tutkimuksen tavoitteena oli parantaa UCNP:itä hyödyntävillä bioaffiniteetti-määrityksillä saavutettavaa analyyttistä herkkyyttä erityisesti poistamalla UCNP:iden epäspesifisestä sitoutumisesta johtuvaa taustasignaalia. Tutkimukseen sisältyi sekä immuno- että hybridisaatiomäärityksiä. Plasmanäytteisiin liittyvää epäspesifistä sitoutumista immunomäärityksissä tutkittiin eristämällä ihmisen plasmasta fraktiot, jotka tuottivat korkeaa taustasignaalia ja tunnistamalla niiden sisältö massaspektrometrillä. Hybridisaatiomäärityksissä koettimien sitoutumista lyhyen kohdesekvenssin kanssa vahvistettiin emäspinoutumisesta johtuvalla vuorovaikutuksella, joka saatiin aikaan hiuspinnirakenteisilla DNA-koettimilla. Lisäksi kehitettiin hybridisaatiokompleksin siirtoon perustuva tekniikka epäspesifisestä sitoutumisesta johtuvan taustasignaalin poistamiseksi. Valtaosa plasmaan liittyvästä taustasignaalista yhdistettiin komplementtiproteiini C1q:hun. Taustasignaali väheni selvästi, kun määrityspuskuriin lisättiin suolaa tai hepariinia. Hybridisaatiomäärityksissä hiuspinnirakenteiset koettimet paransivat analyyttistä herkkyyttä 18-kertaiseksi verrattuna lineaarisiin koettimiin. Lisäksi kompleksinsiirtomenetelmällä onnistuttiin poistamaan epäspesifisestä sitoutumisesta johtuva taustasignaali, jolloin mittalaitteesta tuli pääasiallinen analyyttistä herkkyyttä rajoittava tekijä. Määrityksillä saavutettiin femtoattomolaarisia herkkyyksillä miR-20a:ta vastaavalle DNA-sekvenssille, mikä tekee niistä lupaavia työkaluja mikro-RNA-pohjaiseen diagnostiikkaan.